Provision of HIV services by community health workers should be strengthened to achieve full programme potential: a cross-sectional analysis in rural South Africa - Naidoo, N. (Trop Med Int Health, 2019)
OBJECTIVE: South Africa’s community health workers (CHWs) provide a bridge between the primary healthcare (PHC) facility and its community. We conducted a cross-sectional analysis to determine the contribution of the community-based HIV programme (CBHP) to the overall HIV programme. METHODS: We collected service provision data from the daily activity register of CHWs attached to 12 PHC facilities in rural Mopani District, South Africa. Personal identifiers of individuals referred to the facility for HIV services were recorded and verified against facility routine patient registers to determine effectiveness of referral. RESULTS: HIV services were provided on 18 927 occasions; 30% of the total activities performed by CHWs during the study period. CHWs assessed 12 159 individuals for HIV risk (13% coverage of the study population); only 290 (2%) were referred for HIV testing services. Referral was effective in 213 (73%) individuals; evidence of an HIV-positive status was found for 38 (18%) individuals. However, 30 (79%) of these individuals were referred by CHWs despite being on ART. Adherence support was provided during 5 657 visits; only one individual was referred for complications. Finally, of 864 individuals lost to the ART programme, CHWs managed to find 452 (52%) for referral back to the facility; only 241 (53%) of these were (re)initiated on ART. CONCLUSIONS: Provision of HIV services by CHWs should be strengthened to fully deliver on the programme’s potential. Human resource investment, home-based HIV testing and improved tracing models constitute potential strategies to enhance CHWs impact on the HIV programme.